Transcriptional Regulation of Mouse Tissue-Resident Natural Killer Cell Development - Valero-Pacheco, Nuriban; Beaulieu, Aimee M. (Frontiers in Immunology, 2020)
Natural killer (NK) cells are cytotoxic innate lymphocytes that are well known for their ability to kill infected or malignant cells. Beyond their roles in tumor surveillance and anti-pathogen defense, more recent studies have highlighted key roles for NK cells in a broad range of biological processes, including metabolic homeostasis, immunomodulation of T cells, contact hypersensitivity, and pregnancy. Consistent with the breadth and diversity of these functions, it is now appreciated that NK cells are a heterogeneous population, comprised of specialized and sometimes tissue-specific subsets with distinct phenotypes and effector functions. Indeed, in addition to the conventional NK cells (cNKs) that are abundant and have been well studied in the blood and spleen, distinct subsets of tissue-resident NK cells (trNKs) and “helper” Group 1 innate lymphoid cells (ILC1s) have now been described in multiple organs and tissues, including the liver, uterus, thymus, adipose tissue, and skin, among others. The cNK, trNK, and/or helper ILC1 populations that co-exist in these various tissues exhibit both common and distinct developmental requirements, suggesting that a combination of lineage–, subset–, and tissue–specific differentiation processes may contribute to the unique functional properties of these various populations. Here, we provide an overview of the transcriptional regulatory pathways known to instruct the development and differentiation of cNK, trNK, and helper ILC1s populations in specific tissues in mice.